2010
DOI: 10.1021/jf1017912
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Amino Acids in Chinese Rice Wine by Fourier Transform Near-Infrared Spectroscopy

Abstract: Chinese rice wine is abundant in amino acids. The possibility of quantitative detection of 16 free amino acids (aspartic acid, threonine, serine, glutamic acid, proline, glycine, alanine, valine, methionine, isoleucine, leucine, tyrosine, phenylalanine, lysine, histidine, and arginine) in Chinese rice wine by Fourier transform near-infrared (NIR) spectroscopy was investigated for the first time in this study. A total of 98 samples from vintage 2007 rice wines with different aging times were analyzed by NIR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 39 publications
4
90
1
1
Order By: Relevance
“…In the UV region, 202 and 230 nm were the peaks with the highest responses. These are relative to carboxyl groups of organic acids (Shen et al 2010;Cozzolino et al 2011a;Ferrari et al 2011). Development of multivariate calibration models for pure wine compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the UV region, 202 and 230 nm were the peaks with the highest responses. These are relative to carboxyl groups of organic acids (Shen et al 2010;Cozzolino et al 2011a;Ferrari et al 2011). Development of multivariate calibration models for pure wine compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The chromatogram of the standard mixture and a rice wine sample determined by HPLC-DAD was shown in the previous work (Shen et al, 2010). The result indicated that sixteen free amino acids were detected in the sample according to the retention time of standard mixture.…”
Section: Amino Acid Data Analysismentioning
confidence: 98%
“…All solvents and reagents used in this study were of analytical reagent grade. The detail description of the method was given in a previous work (Shen et al, 2010). Because of laboratory capacity reasons, single sample analysis of amino acids was performed.…”
Section: High-performance Liquid Chromatograph Analysismentioning
confidence: 99%
“…De Mesa-Sronestreet et al (2012) reported that enzymatic extrusion resulted in a highly pure sorghum protein concentrate with a good digestibility. Due to the importance of amino acids in Chinese rice wine, which were not only nutrient components but also precursors for aroma compounds in Chinese rice wine (Shen et al, 2010), enzymatic extrusion pretreatment might also benefit for its nutrition and flavor value.…”
Section: Introductionmentioning
confidence: 99%